SOSIALISASI GOOD CORPORATE GOVERNANCE DAN PRINSIP KEHATI-HATIAN DALAM PENGELOALAAN BANK DI BPR GIANYAR PARTASEDANA, BLAHBATUH – GIANYAR - DHARMAWAN, dkk., NI KETUT SUPASTI (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014, 2014)
The Good Corporate Governance (GCG) regulated under the Regulation of Bank Indonesia No. 8/14/PBI/2006 concerning with the implementation of GCG for Bnks. Although this regulation has already excisted since 2006, many banks do not fully understand how to implement the GCG practically. There are some principles of GCG that need to be considered, namely: Transparency, Accountability, Responsibility, Independency, and Fairness. Besides the GCG, Bank also should implement the principle of prudent banking. Both of those principles are very important for healthy and better future of the banking practice, therefore it needs to be continually socialized. The socialization concerning with GCG and the prudent banking principles as part of community service were conducted in PT. BPR. Gianyar Partasedana, Blahbatuh, on October 30, 2013. Key words : the principles of GCG, the principle of prudent banking, Bank Indonesia Regulation